Exploring The Trends Of The Food And Beverage Industry In Cross-border Mergers And Acquisitions - Pandey, Nistha (ATLAS SkillTech University, 2024)
A Merger is the coming together of two or more businesses into one. Companies may combine to form a new firm or they may merge with another existing company. The assets and liabilities of the target company, also known as the amalgamating company, are acquired by the acquiring company. Shareholders of the merging firm typically accept shares of the merged company in exchange for their interests of the merging company.
Project Report on Exploring The Trends Of The Food And Beverage Industry In Cross-border Mergers And Acquisitions (2022-24) Under the Guidance of Prof. Sweta Kumari
Keywords: Companies; Shareholders; Business